Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Black Family Forest Owners in the Southeastern United States: A Case Study in Six Counties - Amanda Robillard; Cassandra Johnson Gaither; John Schelhas; Brett J Butler (Journal of Forestry, 2024)
The USDA Forest Service, National Woodland Owner Survey asks family forest owners (FFOs) about their attitudes and intentions regarding their forestland. Historically, the number of responses from Black or African American FFOs has been very low, but it is uncertain whether this is because of nonresponse bias or that there are relatively few Black FFOs. To get a better understanding of these FFOs and to test a method to increase response rates, an intensified survey effort was conducted in three southern states: Alabama, North Carolina, and South Carolina. Analyses indicate that Black FFOs have slightly different objectives, activities, and ownership structure for their forestland than their White counterparts, who have traditionally represented the majority of FFOs. Study Implications: By conducting an experiment to increase response rates from Black family forest owners to the National Woodland Owner Survey, we find traditional methodology is not effective. More importantly, we see this group has moderately different responses than their White counterparts. This has wide ranging implications for landowner assistance programs and other initiatives that have been designed on the premise that we are accurately capturing responses from all woodland owners.

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

Dynamics of Large Corporate Forestland Ownerships in the United States - Emma M Sass; Marla Markowski-Lindsay; Brett J Butler; Jesse Caputo; Andrew Hartsell; Emily Huff; Amanda Robillard (Journal of Forestry, 2021)
Ownership of forestland in the United States has changed in recent decades, including the proliferation of timber investment management organizations (TIMOs) and real estate investment trusts (REITs), with the potential to alter forest management and timber supply. This article quantifies forest ownership transitions among ownership categories between 2007 and 2017 and investigates how and why large corporate ownerships own and manage their forestlands. Ownership transitions were determined from refined USDA Forest Service, Forest Inventory and Analysis data; we also conducted a survey of large corporate forestland ownerships. Corporate forestland acreage increased between 2007 and 2017, while family and public forestland decreased. Large corporate landowners report multidimensional, financially focused land management, although industry, timber investment management organizations, real estate investment trusts, and other owners report some different motivations and income streams. This work provides a baseline to track future ownership transitions and the behaviors of large corporate forestland owners.

One Size Does Not Fit All: Relationships between Size of Family Forest Holdings and Owner Attitudes and Behaviors - Brett J Butler; Jesse Caputo; Amanda L Robillard; Emma M Sass; Chris Sutherland (Journal of Forestry, 2021)
An estimated 10 million families, individuals, trusts, and estates own 39 percent of the forestland in the United States, excluding interior Alaska. Using segmented regression, the relationships between size of forest holdings and the attitudes and behaviors of these family forest ownerships were tested using data from the 2018 iteration of the USDA Forest Service’s National Woodland Owner Survey. All 16 variables tested have significant relationships with size of forest holdings, and 13 have one or more breakpoints, ranging from 40 to 5,854 ac, where the relationships between the variables change. Timber as a reason for owning, timber harvesting activities, management plan, advice received, land certified, tax program participation, cost share, recreation, land tenure, recreation, taxes and heirs as concerns, land transfer, and income from forestland have positive relationships with size of forest holdings; resident ownership has a negative relationship; and wildlife as a reason for owning and owner age have mixed relationships.

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)